A community of practice approach to teaching international entrepreneurship - Martina Musteen; Ross Curran; Nuno Arroteia; Maria Ripollés; Andreu Blesa (Administrative Sciences, 2018)
With a dearth of research on international entrepreneurship pedagogy, there is a gap in knowledge on the effectiveness of educational programs, courses, and teaching methods in stimulating and promoting international entrepreneurship practice. To address the gap, this study evaluates an experiential teaching innovation in the area of international entrepreneurship, the Global Board Game project. Designed as a Community of Practice (CoP), the project provides students the opportunity to participate in the construction of their knowledge through interactions with their counterparts in other countries. A qualitative analysis of student essays indicates that the Global Board Game project is effective in helping students achieve learning outcomes, which include defining, recognizing, and evaluating international business opportunities; designing and validating a business model based on such opportunities; and creating a plan for pursuing these opportunities. Additionally, it indicates that participation in the project enhanced students' attitudes toward entrepreneurship as a career path.
Keywords: 350; international entrepreneurship education; Global Board Game project; entrepreneurial intention; active learning; Community of Practice; international student teams